EFFECT OF PH AND CONCENTRATION ON THE REMOVAL OF MAGNESIUM FROM MAGNESIUM CHLORIDE SOLUTION BY BENTONITE - Bibi, Rabia; Shah, Wajid A; Ch, M Iqbal (Biological Sciences - PJSIR, 2004)
By virtue of their well-known cation exchange capacities of clays, particularly bentonites are important minerals to be used as adsorbent of various undesirable ions drained out as industrial waste. One of such pollutant is magnesium containing waste. The removal of magnesium from magnesium containing solutions is found to be dependent both on pH of the solution and the concentration of magnesium ions present in the solution. Using magnesium chloride solution of 50 mg/lit and 100 mg/lit concentration and bentonite (North West Frontier Province), it was found that adsorption equilibrium established within 6 h .